2022
DOI: 10.3390/a15100378
|View full text |Cite
|
Sign up to set email alerts
|

A Method of Accuracy Increment Using Segmented Regression

Abstract: The main purpose of mathematical model building while employing statistical data analysis is to obtain high accuracy of approximation within the range of observed data and sufficient predictive properties. One of the methods for creating mathematical models is to use the techniques of regression analysis. Regression analysis usually applies single polynomial functions of higher order as approximating curves. Such an approach provides high accuracy; however, in many cases, it does not match the geometrical stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 72 publications
(81 reference statements)
0
0
0
Order By: Relevance
“…Nghiên cứu về ứng dụng của thuật toán hồi quy từng đoạn có thể được tìm thấy trong nhiều chủ đề liên quan đến mọi mặt của đời sống. Một nghiên cứu đáng chú ý là nghiên cứu của Al-Azzeh và các cộng sự, xuất bản năm 2022 về phương pháp ứng dụng thuật toán hồi quy từng đoạn vào việc tăng độ chính xác của những mô hình toán học [13].…”
Section: Xây Dựng Công Cụ Học Máyunclassified
“…Nghiên cứu về ứng dụng của thuật toán hồi quy từng đoạn có thể được tìm thấy trong nhiều chủ đề liên quan đến mọi mặt của đời sống. Một nghiên cứu đáng chú ý là nghiên cứu của Al-Azzeh và các cộng sự, xuất bản năm 2022 về phương pháp ứng dụng thuật toán hồi quy từng đoạn vào việc tăng độ chính xác của những mô hình toán học [13].…”
Section: Xây Dựng Công Cụ Học Máyunclassified
“…Research on the application of the piecewise regression algorithm can be found in many topics related to all aspects of life. One of the notable studies is the research by Al-Azzeh et al, on the method of applying the piecewise regression algorithm to increase the accuracy of mathematical models [13].…”
Section: Algorithm Selectionmentioning
confidence: 99%